Potential Roles of the Free Salivary Microbiome Dysbiosis in Periodontal Diseases - Diao, Jing; Yuan, Chao; Tong, Peiyuan; Ma, Zhangke; Sun, Xiangyu; Zheng, Shuguo (Frontiers in Cellular and Infection Microbiology, 2021)
Saliva is a vital mediator in the oral cavity. The dysbiosis of free bacteria in saliva might be related to the onset, development, prognosis, and recurrence of periodontal diseases. Whereas the relationship is still unclear. The objective of this study was to investigate the potential roles of the free salivary microbiome in different periodontal statuses, their reaction to non-surgical periodontal therapy, and the differences between diseased individuals after treatment and healthy persons. We recruited 15 healthy individuals and 15 individuals with gingivitis and 15 individuals with stage I / II generalized periodontitis. A total of 90 unstimulated whole saliva samples were collected and sequenced using the full-length bacterial 16S rRNA gene sequencing. We found that as the severity of disease increased, from health to gingivitis and periodontitis, the degree of dysbiosis also increased. Higher abundance of Prevotella intermedia, Catonella morbi, and lower abundance of Porphyromonas pasteri, Prevotella nanceiensis, Haemophilus parainfluenzae might be the biomarkers of periodontitis with the AUC reaching 0.9733. When the patients received the supragingival scaling, there were more pathogens related to recolonization in saliva of periodontitis patients than healthy persons. Even after effective non-surgical periodontal therapy, individuals with periodontitis showed a more dysbiotic and more pathogenic microbial community in saliva than healthy individuals. Therefore, the gradual transition in the entire salivary microbial community from health to disease was a gradual shift of dysbiosis. The free salivary pathogens might play an important role in the recolonization of bacteria and the prognosis and recurrence of periodontal diseases.